Sleep disturbances and progression of mobility disability: Longitudinal findings from the Nurses’ Health Study - Daniel Whibley; Monica M. Shieu; Galit Levi Dunietz; Tiffany J. Braley (Sleep Epidemiology, 2024)
Objective: To examine longitudinal associations between self-reported sleep disturbances and mobility disability progression among women, including subgroups with multiple sclerosis (MS), diabetes, and osteoarthritis (OA). Methods: Prospective cohort study using data from Nurses’ Health Study long-form questionnaires (2008, 2012, 2014, 2016). Logistic regression was used to quantify associations between sleep-related variables at baseline and subsequent increase in mobility disability. Results: Of 70,303 women (mean age 73), 392 had MS, 7,302 had diabetes, and 24,099 had OA. Between 2008–2016, mobility disability increased by 16.9 % overall, 27.8 % in the MS subgroup, 27.0 % in the diabetes subgroup, and 23.7 % in the OA subgroup. Known/suspected obstructive sleep apnea was significantly associated with an increase in mobility disability between 2008 and 2016, overall (OR:1.4, 95 %CI:1.2,1.5), and in the diabetes (OR:1.5, 95 %CI:1.2,1.9) and OA subgroups (OR:1.2, 95 %CI:1.0,1.4), but not in the MS subgroup (OR:2.3, 95 %CI:0.6,8.9); however, across 2012–2016, this association was significant for MS (OR:4.0, 95 %CI:1.0,16.1). Suboptimal sleep duration was significantly associated with increased odds of mobility disability progression overall, but not in disease subgroups. Perception of adequate sleep was associated with lower odds of mobility disability progression overall (OR:0.82, 95 %CI:0.78,0.87) and for the OA subgroup (OR:0.83, 95 %CI:0.76,0.91). Excessive daytime sleepiness was associated with mobility disability progression overall (OR:1.2, 95 %CI:1.1,1.4) and for the OA subgroup (OR:1.2, 95 %CI:1.0,1.4). Conclusions: Prevalent sleep disturbances could increase disability progression among women. Chronic disease populations may be uniquely vulnerable. Informed by these data, future research could offer new insight into sleep-based strategies to ameliorate mobility decline.